Some remarks on ‘after development’ of Malaysia. - Heng Siam-Heng, (Universiti Kebangsaan Malaysia, 2008)
The 5" International Malaysian Studies Conference was held on 8-10 August 2006 at Universiti Putra Malaysia. The theme of the conference is 'After Development' in Malaysia: Reflections on the Development Agenda and the .- Future, and there was a special plenary session held on this theme. This short piece is an extended version of the observations and remarks made by me at the plenary session. The conference document carries the following passage with a deep message: Having gone through this journey of several decades of economic development, largely under the influence of development theorists and a developmentalist leadership bent on 'catching up' with the developed West and to leapfrog to become a developed nation, it is time for Malaysian scholars and Malaysianists to reflect on this process of development, its consequences and effects, and what the future might hold if we are to continue on the same trajectory, as well as to reflect on the fate of development studies. Such reflection and rethinking is not only timely but also necessary. Tbis is especially so at a time when material development has dominated and subvertqd human development, when poverty and inequality seem to persist, and when the promises of a just and equitable society irrespective of race, colour, creed and gender remain largely a mirage. At the same time, such rethinking is equally necessary so that we can look afresh at development studies - a highly influential body of knowledge several decades ago but has been cast aside by the neoliberal push towards market fundamentalism and the bef ef in the minimalist role of the state. The rest of this paper is very much inspired by the reflective mood and the challenges contained in the above passage.